2020
DOI: 10.2147/opth.s194234
|View full text |Cite
|
Sign up to set email alerts
|

<p>Therapeutic Potential of the Ranibizumab Port Delivery System in the Treatment of AMD: Evidence to Date</p>

Abstract: Age-related macular degeneration (AMD) is one of the leading causes of blindness in older adults worldwide. The advent of intravitreal neutralization of vascular endothelial growth factor (VEGF) has revolutionized the management of patients with neovascular AMD, but current anti-VEGF therapies carry a high threshold of patient burden. The ranibizumab port delivery system (PDS) is an implanted, refillable reservoir that continuously supplies the anti-VEGF medication ranibizumab directly into the vitreous, elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Despite recent advances in the treatment of CNV for wet AMD with anti-vascular endothelial growth factor A (VEGF) agents [ 23 ], anti-VEGF treatments remain ineffective for some patients and a significant proportion of these patients still develop severe visual loss and progress to legal blindness over time [ 24 ]. Recent evidences point to the possibility of an association between anti-VEGF therapy and progression of geographic atrophy [ 25 ]. There is currently no satisfactory treatment for the dry form of AMD, although clinical trials have investigated an increasing number of therapeutic options [ 26 ] (Table 1 ).…”
Section: Amd Pathophysiologymentioning
confidence: 99%
“…Despite recent advances in the treatment of CNV for wet AMD with anti-vascular endothelial growth factor A (VEGF) agents [ 23 ], anti-VEGF treatments remain ineffective for some patients and a significant proportion of these patients still develop severe visual loss and progress to legal blindness over time [ 24 ]. Recent evidences point to the possibility of an association between anti-VEGF therapy and progression of geographic atrophy [ 25 ]. There is currently no satisfactory treatment for the dry form of AMD, although clinical trials have investigated an increasing number of therapeutic options [ 26 ] (Table 1 ).…”
Section: Amd Pathophysiologymentioning
confidence: 99%
“…The success of traditional anti-VEGF therapies raised the question of whether a longer-acting ranibizumab could be delivered via an implantable reservoir. Thus, the Port Delivery System (PDS) was developed, allowing for the continuous release of ranibizumab into the vitreous via passive diffusion [ 38 ]. PDS is intended to reduce the frequency of intravitreal injections and potentially allow patients with nAMD to go several months before needing a refill of the implant.…”
Section: Emerging Neovascular Amd Therapiesmentioning
confidence: 99%
“…Another clinical trial studied the efficacy of a refillable ranibizumab port delivery system in patients with a neovascular form of AMD (Lucentis, Genentech), which consists of a sustained release reservoir (the study has now passed phase 1). 64 , 65 This system is aimed to reduce the number of required repeated IVIs. The study also showed that the mean number of system refills was 4.8/patient/12 months.…”
Section: Discussionmentioning
confidence: 99%